Ethnobotanical importance of Asteraceae plants among Tharu tribe in Udham Singh Nagar, Uttarakhand, India - Sheetal Sharma; Sneh Lata (Ethnobotany Research and Applications, 2022)
Background: Uttarakhand, a hilly state of northern India is gifted with unique natural beauty, rich biodiversity and great ethnic diversity. Asteraceae is the largest dicot family in the state and its several species are utilized by Tharu tribes for their livelihood. The present study was aimed to explore and document the ethnobotanical importance of Asteraceae plants used by Tharu community. Methods: The study area was visited frequently and a total of 104 Tharu informants from 11 villages were interviewed with the help of a semi structured questionnaire. Collected plant specimens were identified and processed for herbarium in the laboratory. Ethnobotanical data were analyzed using Use value (UV) and Factor informant consensus (Fic). Results: A total of 51 plants belonging to 38 genera under 12 tribes of Asteraceae family were found to be useful among Tharu people. Most of the species (50.98%) were noted to be used for curing various diseases. They use several plants for fodder (33.33%), ornament (27.45%), veterinary medicines (9.80%), social ceremonies (5.88%), and other purposes (13.72%) too. Quantitative analysis of data shows that Tagetes erecta has the highest use value (0.9423) followed by Ageratum houstonianum (0.4615) and Eclipta prostrata (0.3653). Maximum homogeneity was recorded in constipation, earache, eye disorders, heat stroke, infertility, paralysis, fuel and food. Conclusions: The present study concludes that several Asteraceae plants have high use value and play an important role in Tharu’s daily life. The recorded precious ethnobotanical data with UV and Fic analysis will be useful to the future researchers for further phytochemical, pharmacological, conservation and other studies. Keywords: Asteraceae, Tharu, Ethnobotany, Udham Singh Nagar.